Implementasi Surat Pemesanan PT ADE Dengan Menggunakan ZOHO Form - Adinda Anastasya Febi Valentina; Anisa Ika Wardhani; Bernadeta Winda Putri Permatasari; Nurhasan Hamidi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Digitalization carried out by companies has an impact on marketing parties to carry out the ordering process online. Meanwhile, marketing parties need time to adapt to technology. The purpose of implementing the dedication to PT Atmi Duta Engineering is to increase knowledge and insight so that the marketing division sales can use Zoho Form sales for online forms. Given the lack of knowledge about how to create a questionnaire using the Zoho Form application. Implementation of dedication to PT Atmi Duta Engineering using observation and interview methods. Based on the results of the trial and outreach, it shows that the marketing division finds it helpful in filling out order letters and it is easy for the admin to manage order data.